#TITLE_ALTERNATIVE# - PRATAMA PURBA (NIM 13103022), BAYU
A piping system is an economical and efficient transport system for distributing oil and natural gas. One of its most important components is its support. Supports prevent the piping system from failing or experiencing malfunction during heavy-load operations. Supports are generally built above ground; some piping systems even directly use the ground itself as its supports system. If the surface on the ground is lowered, the supports above it will also be lowered. This could reduce the effectiveness of the supports. This problem has led Laboraturium Dinamika Pusat Rekayasa Industri ITB to begin research on the usage of flexible supports on piping systems, in order to increase its effectiveness. This undergraduate work has done testing that compares the effectiveness of stiff support and flexible support in compensating the lowering of the soil. Besides testing, research is also done with finite element modeling. The models may be used to preview the force changes in the supports, deflections, and the strain changes in the pipe systems during lowering of supports. The results gotten from this work has shown that the usages of flexible supports are more effective in compensating for the lowering of soil. The finite element models also can be used to reflect that force changes in the supports, deflections and strain happens in the piping system when supports are lowered.